2005
DOI: 10.1017/s0950268805004711
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination and early protection against non-host-specific Salmonella serotypes in poultry: exploitation of innate immunity and microbial activity

Abstract: A recent European Union Directive required member states to put monitoring and control programmes in place, of which vaccination is a central component. Live Salmonella vaccines generally confer better protection than killed vaccines, because the former stimulate both cell-mediated and humoral immunity. Administering Salmonella bacteria orally to newly hatched chickens results in extensive gut colonization and a strong adaptive immune stimulus but broiler chickens are immunologically immature. However, coloniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(110 citation statements)
references
References 160 publications
2
105
1
2
Order By: Relevance
“…This high susceptibility has been associated with the absence of normal gut microbiota [3,4] and the immature immune system of young chickens [5][6][7]. As a consequence, classical vaccination is not an effective means to achieve protection against Salmonella infection during the first days of life [14]. Alternatively, the use of organic acids, essential oils, proand prebiotics as feed supplements can help to control Salmonella infections in broiler chickens, but the protective responses elicited by these compounds only start several days post-hatch [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This high susceptibility has been associated with the absence of normal gut microbiota [3,4] and the immature immune system of young chickens [5][6][7]. As a consequence, classical vaccination is not an effective means to achieve protection against Salmonella infection during the first days of life [14]. Alternatively, the use of organic acids, essential oils, proand prebiotics as feed supplements can help to control Salmonella infections in broiler chickens, but the protective responses elicited by these compounds only start several days post-hatch [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research showed that the colonisation-inhibition effect is more pronounced between isogenic strains and that there is greater inhibition within a serovar than between serovars [14,16,27]. Consequently, it is likely that the Salmonella Typhimurium hilAssrAfliG strain is not able to inhibit strains belonging to other serovars than Typhimurium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearance of primary S. Enteritidis and S. Typhimurium infection is dependent on age of the chicken and host genetics (Beal and Smith, 2007). Cell-mediated immunity plays a more important role than the humoral response in protection and against Salmonella infection (Van Immerseel et al, 2005). Wigley et al (2005) have demonstrated that at the onset of laying both the T-cell response to Salmonella and non-specific responses to mitogenic stimulation fall sharply in both infected and noninfected birds.…”
Section: Resistance and Immune Response Of Poultry To Salmonella Withmentioning
confidence: 99%
“…Mutants were constructed in an identical way to the proton translocating-deficient mutants described previously (46). In brief, four primers were designed for each gene to be mutated such that two fragments close to the 5' and 3' ends ( Transductants were plated on LB agar containing spectinomycin or kanamycin and after incubation at 37C/24h…”
Section: Mutant Constructionmentioning
confidence: 99%